Investigasi sifat mekanis sambungan Dissimilar Friction Stir welding (DFSW) Aluminium Alloys (AA5052 to AA6061) - Muhammad Arsyad Suyuti; Apollo .; Muhammad Iswar; Rusdi Nur (Jurnal Energi Dan Manufaktur, 2020)
The joint for two different materials (AA5052 and AA6061) can be done by the Dissimilar Friction Stir Welding (DFSW) process. Therefore, this study was conducted to analyze the mechanical properties of dissimilar welding joints. In this study the DFSW process uses a tool with a shoulder Ø 17.8 mm and a cylindrical pin Ø 5 mm. FSW blocking is done on conventional milling machines with 1300 rpm, 1950 rpm and 2850 rpm tool rotation variations, while the welding speed variations are 43 mm / min, 130 mm / min and 240 mm / min. The results of mechanical properties testing showed the highest hardness value obtained was 55.3 HBN at 1300 rpm with 240 mm / min feeding, the highest tensile strength occurred for 1300 rpm and 240 mm / min feeding at 123.51 MPa. The fracture of the tensile test results generally occurs in the HAZ area and the AA5052 base metal Nugget. Investigation results show that the DFSW connection of aluminum alloy material AA 6061 and AA 5052 adapt is well connected, but in terms of general strength the tensile strength of the joint (HAZ and Nugget) is smaller than the tensile strength of the base metal. This DFSW connection adaptation is applied to connections that do not accept load or tensile strength due to the load received by the connection not to exceed the maximum tensile strength of base metal AA 5052